Towards an 'African Medical Humanities': Examining Mental Health in Nigerian Contemporary Literature through an African-Centred Approach (Altre Modernità, 2024)
The significance of adopting an African-centric approach when examining traditional West African medicine and cultural practices related to healthcare and the body cannot be overstated. In the fields of humanities and social sciences, there has been a tendency to prioritize Euro-centric scholarship at the expense of exploring the belief systems of people of African descent. However, recognising the West African indigenous world-view is a crucial first step in challenging Euro-American epistemological dominance and enabling a more comprehensive analysis of healthcare practices.Against this backdrop, the present research proposes the term ‘African Medical Humanities’ with the aim of deconstructing Euro-centric universalism and offering an alternative framework for studying health-related phenomena in sub-Saharan African creative writing. Specifically, the analysis will focus on the works of two Nigerian contemporary writers by examining the Abiku/ogbanje (spirit child) motif in relation to mental health and traditional African therapeutics.The study will pay particular attention to Helen Oyeyemi’s The Icarus Girl (2005) and Akwaeke Emezi’s Freshwater (2018), investigating how these works address mental health and personhood within indigenous therapeutics among West African societies. Through this analysis, the present contribution demonstrates how spirituality is deeply embedded in traditional healthcare practices, thereby reflecting the importance of adopting an African-centric approach to understanding healthcare and the body in West African societies.